2021
DOI: 10.1016/j.radcr.2021.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pelvic alignment in a woman before and after childbirth, using three-dimensional pelvic models based on magnetic resonance imaging: A longitudinal observation case report

Abstract: 3-dimensional pelvic models based on magnetic resonance images (MRI) can be used to investigate accuracy and specifics of changing pelvic alignment during pregnancy and after childbirth. Few studies have investigated changes of pelvic alignment during pregnancy and after childbirth using three-dimensional pelvic models. This case report documents the changes of pelvic alignment during late pregnancy and after childbirth using MRI-based three-dimensional (3D) pelvic models. This was a longitudinal observation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Most of the data present explores pelvic changes in patients without this history. A case study by Sakamoto et al 8 documented pelvic alignment changes by MRI in a Japanese primipara woman with imaging at 28 weeks estimated gestational age, 39 weeks estimated gestational age, and both 4 and 72 weeks postpartum. The authors demonstrated an increased distance between the posterior superior iliac spine and the pubic symphysis during gestation, which then markedly decreased by 4 weeks postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the data present explores pelvic changes in patients without this history. A case study by Sakamoto et al 8 documented pelvic alignment changes by MRI in a Japanese primipara woman with imaging at 28 weeks estimated gestational age, 39 weeks estimated gestational age, and both 4 and 72 weeks postpartum. The authors demonstrated an increased distance between the posterior superior iliac spine and the pubic symphysis during gestation, which then markedly decreased by 4 weeks postpartum.…”
Section: Discussionmentioning
confidence: 99%